Biogas production enhancement using semi-aerobic pre-aeration in a hybrid bioreactor landfill. (September 2016) - Cossu, Raffaello; Morello, Luca; Raga, Roberto; Cerminara, Giulia
Highlights: Pre-aeration to enhance methane production in the following anaerobic phase. Performance based transition from semi-aerobic to anaerobic phase. Methane production and kinetics increased under low-regime intermittent pre-aeration. Abstract: Landfilling continues to be one of the main methods used in managing Municipal Solid Waste (MSW) worldwide, particularly in developing countries. Although in many countries national legislation aims to reduce this practice as much as possible, landfill is a necessary and unavoidable step in closing the material cycle. The need for innovative waste management techniques to improve landfill management and minimize the adverse environmental impact produced has resulted in an increasing interest in innovative systems capable of accelerating waste stabilization. Landfill bioreactors allow decomposition kinetics to be increased and post-operational phase to be shortened; in particular, hybrid bioreactors combine the benefits afforded by both aerobic and anaerobic processes. Six bioreactor simulators were used in the present study: four managed as hybrid, with an initial semi-aerobic phase and a second anaerobic phase, and two as anaerobic control bioreactors. The main goal of the first aerated phase is to reduce Volatile Fatty Acids (VFA) in order to increase pH and enhance methane production during the anaerobic phase; for this reason, air injection was stopped only when these parameters reached the optimum range for methanogenic bacteria. Biogas and leachate were constantly monitored throughout the entire methanogenic phase with the aim of calibrating a Gompertz Model and evaluating the effects of pre-aeration on subsequent methane production. The results showed that moderate and intermittent pre-aeration produces a positive effect both on methane potential and in the kinetics of reaction.